2013
DOI: 10.1249/mss.0b013e318285f202
|View full text |Cite
|
Sign up to set email alerts
|

Walking Objectively Measured

Abstract: Purpose This study developed and tested an algorithm to classify accelerometer data as walking or non-walking using either GPS or travel diary data within a large sample of adults under free-living conditions. Methods Participants wore an accelerometer and a GPS unit, and concurrently completed a travel diary for 7 consecutive days. Physical activity (PA) bouts were identified using accelerometry count sequences. PA bouts were then classified as walking or non-walking based on a decision-tree algorithm consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 31 publications
(40 reference statements)
3
49
1
Order By: Relevance
“…Kang et al (8) compared GPS-derived minutes/day of walking/running to travel diary-derived walking/running and found that GPS overestimated walking/running by 17.5% (slightly higher than the bias estimates in the present study), but other modes were not investigated. Minutes/day in each mode are frequently the final travel variables derived from GPS that are used in statistical analyses in health studies.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Kang et al (8) compared GPS-derived minutes/day of walking/running to travel diary-derived walking/running and found that GPS overestimated walking/running by 17.5% (slightly higher than the bias estimates in the present study), but other modes were not investigated. Minutes/day in each mode are frequently the final travel variables derived from GPS that are used in statistical analyses in health studies.…”
Section: Discussioncontrasting
confidence: 76%
“…PALMS allows users control over parameter settings for trip detection and mode classification algorithms. The major trip-related settings were informed from empirical testing and existing algorithms (2, 6, 7, 8, 16, 21, 23, 27) and are described in detail below. Information on the other parameter settings (of less relevance to the present study) used in the scoring protocol can be obtained by contacting the first author.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process by which accelerometer data were integrated with GPS and travel log information to identify walking and non-walking physical activity bouts is described elsewhere in detail (17). In summary, bouts of ≥5 minutes of accelerometer counts >500 per 30-second epoch, allowing for up to 2 minutes of counts below the 500-count threshold, were considered to be physical activity (PA) bouts.…”
Section: Methodsmentioning
confidence: 99%
“…As the number of willing participants exceeded the number of monitors available, monitors were sent to a random sample of willing participants in batches as described in a previous paper [19]. In 2010 and 2011, the sub-sample who had completed a questionnaire and provided valid accelerometer data in 2009 were invited to wear a combined heart rate and movement sensor and a GPS device, and to complete a questionnaire and a detailed travel diary.…”
Section: Methodsmentioning
confidence: 99%